2011
DOI: 10.4314/pamj.v9i1.71210
|View full text |Cite
|
Sign up to set email alerts
|

Atopic dermatitis in Tunisian schoolchildren

Abstract: IntroductionThe prevalence of atopic dermatitis (AD) is low in North Africa. We describe the epidemiology of this atopic condition among school children in Tunisia.MethodsWe conducted a Cross-sectional survey study of 5 to 6-year-old schoolchildren from 21 primary schools of Sfax. The diagnosis of AD was based on the U.K. Working Party diagnostic criteria. A questionnaire including these criteria and some risk factors of AD was issued to the children. All children were examined by one dermatologist.ResultsAmon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
0
4
1
2
Order By: Relevance
“…This is in agreement with study conducted in Sweden [ 36 ], Yerevan [ 33 ], and Iran [ 31 ] and systemic review in European countries [ 34 ] which showed a significant association to AD. However, it is in contrary to the findings from Tunisia [ 29 ] and Ethiopia at Jimma [ 13 ].…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…This is in agreement with study conducted in Sweden [ 36 ], Yerevan [ 33 ], and Iran [ 31 ] and systemic review in European countries [ 34 ] which showed a significant association to AD. However, it is in contrary to the findings from Tunisia [ 29 ] and Ethiopia at Jimma [ 13 ].…”
Section: Discussioncontrasting
confidence: 93%
“…The finding is slightly higher than studies conducted in the country at Ankober mobile clinic which was 4.67 % [ 23 ], and at Jimma 4.4 % [ 13 ]. However, it is less compared to studies from America 11 % [ 26 ], Argentina 41.1 % [ 27 ] and Japan 18.6 % [ 28 ] but still higher from the Tunisian study of 0.65 % [ 29 ]. The difference in the proportion of AD reported among the studies might be due to the geographical difference, use of different diagnostic criteria for diagnosis and the age group considered, study season and period.…”
Section: Discussionmentioning
confidence: 77%
“…In Tunisia, 1617 children were involved in determining the prevalence of AD in 2007. A result of 0.65% prevalence of AD was reported among five to six years old Tunisian children [ 59 ]. Next, Namibian adolescents aged between 15 to 30 years old reported having a prevalence of 43.3% during a study conducted in 2014 [ 60 ].…”
Section: Global Epidemiology Of Admentioning
confidence: 99%
“…4 Berdasarkan status penderita didapatkan faktor pencetus terbanyak ialah faktor genetik atau memiliki riwayat atopik yaitu 44 (37,61%) kasus (Tabel 4). Penelitian yang dilakukan Amouri et al 15 di Singapura mendapatkan 69,3% kasus memiliki riwayat atopi personal yaitu rinitis alergi 34,5%, asma 9,5%, serta rinitis alergi dan asma 25,5%. 15 Pada penelitian di Spanyol yang dilakukan oleh Aragounes et al 17 didapatkan sebanyak 55% pasien DA memiliki riwayat atopi personal rinitis alergi (26%), asma (19%), dan alergi makanan (12%).…”
Section: Metode Penelitianunclassified
“…Penelitian yang dilakukan Amouri et al 15 di Singapura mendapatkan 69,3% kasus memiliki riwayat atopi personal yaitu rinitis alergi 34,5%, asma 9,5%, serta rinitis alergi dan asma 25,5%. 15 Pada penelitian di Spanyol yang dilakukan oleh Aragounes et al 17 didapatkan sebanyak 55% pasien DA memiliki riwayat atopi personal rinitis alergi (26%), asma (19%), dan alergi makanan (12%). 16 Sejumlah survei berbasis populasi menunjukkan bahwa risiko anak yang memiliki atopik lebih besar ketika ibunya memiliki atopik daripada ayahnya.…”
Section: Metode Penelitianunclassified